Hold fast to dreams - Pinkney, Andrea Davis (New York : Morrow Junior Books, 1995)
Twelve-year-old Deirdre, whose passion for photography has earned her the nickname "Camera Dee," feels uncomfortable being the only black student at her new school.
Keywords: Moving, Household -- Fiction; Prejudices -- Fiction; Photography -- Fiction; African Americans -- Fiction